The Development of E-Book Based on Multiple Intelligence to Train Critical Thinking Skill on Cell Division Topic - Rizqy Amalya Sofa; Sifak Indana (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2021)
Critical thinking skill is one of the thinking skill that students must have to face global competition in the 21st century. E-book is one of the alternative teaching materials that can be used in distance learning. E- book combined with multiple intelligences theory can facilitate every type of students’ intelligence in receiving and processing information so it can maximize students’ critical thinking skill. One of the Biology topics that was considered difficult by students and demanded critical thinking skills was cell division topic. The purpose of this research was to develop an e-book based on multiple intelligence to train critical thinking skills on cell division topics that are valid and practical. This research used ADDIE model. The e-book was tried out limited to 10 students of SMAN 1 Cerme grade 12th. The validity of the e-book is determined from the validation result of education experts, material experts, and biology teachers in terms of content, presentation, and language component. The practicality of the e-book is determined by students’ responses to e-book usage. The data analysis technique was carried out by descriptive quantitative. The result of the validity analysis showed an average percentage score of 95% with a very valid category. The practicality of e-book usage showed an average percentage score of 96.53% with a very practical category. Based on the result, it can be concluded that e-book based multiple intelligence to train critical thinking skill on cell division topic is declared valid and practical to be used in the learning process.